Insights into membrane protein-lipid interactions from free energy calculations - Corey, R; Vickery, O; Sansom, M; Stansfeld, P (American Chemical Society, 2019)
Integral membrane proteins are regulated by specific interactions with lipids from the surrounding bilayer. The structures of protein−lipid complexes can be determined through a combination of experimental and computational approaches, but the energetic basis of these interactions is difficult to resolve. Molecular dynamics simulations provide the primary computational technique to estimate the free energies of these interactions. We demonstrate that the energetics of protein−lipid interactions may be reliably and reproducibly calculated using three simulation-based approaches: potential of mean force calculations, alchemical free energy perturbation, and welltempered metadynamics. We employ these techniques within the framework of a coarse-grained force field and apply them to both bacterial and mammalian membrane protein−lipid systems. We demonstrate good agreement between the different techniques, providing a robust framework for their automated implementation within a pipeline for annotation of newly determined membrane protein structures.